2016
DOI: 10.1039/c5ra27405b
|View full text |Cite
|
Sign up to set email alerts
|

Efficiently amplified ultrasonic degradation of spherical polyelectrolyte brushes by a magnetic field

Abstract: This work describes a facile and green method about the ultrasonic degradation of polymer chains amplified by magnetic field.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Changes in polymer structure can be created during ultrasonic treatment as a result of cavitation and research has suggested that chain cleavage could occur preferentially at weak spots in the chain [36]. PS@PSS hairy nanoparticles used in this paper is a special fuzzy structure of dense core and loosened shell, so the thickness decrease in PS@PSS shown in Table 2 happened gradually from the chains outside to the inner side [37].…”
Section: Resultsmentioning
confidence: 99%
“…Changes in polymer structure can be created during ultrasonic treatment as a result of cavitation and research has suggested that chain cleavage could occur preferentially at weak spots in the chain [36]. PS@PSS hairy nanoparticles used in this paper is a special fuzzy structure of dense core and loosened shell, so the thickness decrease in PS@PSS shown in Table 2 happened gradually from the chains outside to the inner side [37].…”
Section: Resultsmentioning
confidence: 99%
“…In the presence of the magnetic field, sonochemical efficiency increased 10-fold. Amplification of the magnetic field helped to decrease the viscosity of brush solution by boosting acoustic cavitation ( Zhang et al, 2016 ).…”
Section: Mechano-thermo-photo Irradiative and Green Chemical (Pre)treatment Of Plasticsmentioning
confidence: 99%
“…Narrowly distributed hairy nanospheres (HNs) were prepared by the combination of conventional emulsion polymerization and photoemulsion polymerization according to our previous work [32][33][34]. First, a photoinitiator was generated on the core under the conditions of avoiding light.…”
Section: Synthesis Of Hairy Nanospheres (Hns)mentioning
confidence: 99%